Analysis of the final actions used in basketball during formative years according to player's position - Ortega, E.; Cardenas, D.; Sainz de Baranda, P.; Palao, J. M. (Journal of Human Movement Studies, 2006)
The purpose of this study was to analyse and compare the way that players, in formative years, end their ball possessions during competition according to player position. One hundred and eighty-four under-16 basketball players (37 point-guards, 32 off-guards, 61 small-forwards, 21 power-forwards, and 36 centers) were analysed during 24 games. The analysed variables were: shots, passes, interceptions or steals, interruptions, violations, personal fouls received, personal fouls committed, Jump balls, and other actions. The results show differences in the shot actions, äs the point-guards and power-forwards shoot the most often and have the best percentage in two-point shots and free-throws. In three-points shots, the point-guards shoot the most often and have the best percentage. Also, significant differences in the number of passes, steals and violations between the point-guards and the rest of the players are found. The data shows differences between point-guards and power-forwards with the rest of the players in the personal fouls received and the points made. These results show the use of play styles of senior teams in formation years, in which each player is specialised in specific actions. These results show the necessity of adapting game style and rules to the characteristics of the youth players and not vice-versa.